Temporary Job and its Impact On Employee Performance (Global Journal of Management and Business Research, 2011)
Employees are our valuable asset. Objective of an organization can be met with the help of its employees. There are a number of factors on which performance of an employee is depending. Purpose of this research paper is to find how dependent variable employee performance relates to independent variable contract job with facets of uncertainty, loyalty and perks (incentives). Employees have strong association toward job security and incentives. Correlation results show that performance has positive relation with loyalty and incentives but negative with job uncertainty. Between independent variables loyalty shows positive relation with incentives and negatively related with uncertainty. Employee#x2019;s performance makes an organization leading in market. To retain their employees it is recommended to provide them job security and to appreciate their work incentives should be provided.
Keywords: Uncertainty; contractual or temporary job; perks or incentives; loyaltyand employee performance